Backward erosion piping mechanism in dike foundations with and without landside blanket layers: numerical simulation of size effects - Qiuling Yao; Xiping Yan; Zebin Wu; Huiqing Hao; Meihong Ma; Meihong Ma (Frontiers in Earth Science)
IntroductionThis study investigates the backward erosion piping mechanism and its dependency on model size through both experiments and numerical simulations. The objective is to understand how different model dimensions affect the hydraulic gradients and piping behavior in dike systems.MethodsNumerical simulations were performed using the finite element method (FEM), where the dike foundation was modeled in 3D and seepage flow was simulated under various hydraulic gradients. Physical experiments were also conducted using small-scale dike models to verify the numerical results and study the effects of model size.Results and DiscussionThe results show that in dikes without blanket layers, hydraulic gradients increase steadily as the piping channel develops, leading to upstream erosion and failure. In contrast, dikes with a blanket layer exhibit a stabilizing effect: the hydraulic gradient initially decreases before increasing, leading to a self-healing phenomenon that halts further channel progression. The study further reveals that the size effect—indicated by hydraulic gradients—diminishes with larger model dimensions and becomes negligible beyond a certain threshold. Additionally, the interaction between model width and depth significantly influences the progression of piping. These findings offer valuable insights for designing more resilient dike systems and improving flood protection strategies.